76.1k views
0 votes
What is the length of the unknown leg

What is the length of the unknown leg-example-1

1 Answer

3 votes

Answer:

6 mm

Explanation:

Use the Pythagorean Theorem to solve for the unknown leg


a^(2) +b^(2)=c^(2)

Since we need to solve for a, we will manipulate the equation in terms of b and c →
a=\sqrt{c^(2)-b^(2) }

Here, b = 7 mm and c =
√(85) mm

Plugging these numbers into our equation gives us
a=\sqrt{(√(85))^(2) -(7)^(2) }
√(85-49) =
√(36) = 6 mm

User Kayak
by
5.4k points